Opacity and saturable absorption in solid-density plasmas generated by an x-ray free-electron-laser - Rackstraw, D (2015)
The arrival of 4th generation light-sources has opened up new regimes in x-ray–matter interactions. A billion times spectrally brighter than the preceding x-ray sources, free-electron-lasers (FELs) can deposit large amounts of energy into a system in less than 100 fs. Since the absorption of x-rays is reasonably well understood and the pulse length is so short, the plasma conditions created are well characterized. The work presented in this thesis relates to a series of experiments where solid aluminium foils were heated with the focussed FEL radiation. The way that the opacity of the FEL heated foil would affect the observed emission spectrum is investigated. The extent to which the opacity influences the emission spectra is found to have intensity and photon energy dependencies. The transmission of the x-ray pulse used to generate a solid-density aluminium plasma is studied in both simulation work using the collisional-radiative code SCFLY and experiment. The phenomenon of saturable absorption is seen to occur, caused by the system being ionized to such an extent that none of the ions present can absorb the x-ray photons through K-shell photoionization. The use of the FEL beam in a split and delay scheme was also explored. Simulations of the time dependent changes in transmission and what may be observed were performed.